The Archeology of Knowledge in Parikan of Kentrung Arts - Maisaroh, Siti; Mu’minin; Dia, Eva Eri; Ahya, Akhmad Sauqi; Wahyuniarti, Fitri Resti; Wiyanto, Muhammad Saibani (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The research entitled Archeology of Knowledge in the Parikan of Kentrung Art that focused on the following three things: (1) knowledge of the structure of the Kentrung art shrine; (2) knowledge of the value or meaning content of the Kentrung art shrine; and (3) knowledge of the function of the Kentrung art shrine. The archaeological approach and theory of knowledge are used to view art (especially parikan structures) as a form of expression of cultural values and community concerns in the form of symbols that require interpretation, understanding, and explanation. This research employed both descriptive qualitative research methods and folklore research methods during the data collection phase. We use qualitative research methods to verbally describe the data, while we use folklore research methods to process the oral data found in Parikan of Kentrung Art. Both have three stages, namely data collection, data classification, and data analysis. The results of the data analysis concluded that (1) structure knowledge of the parikan of kentrung art includes: each stanza consists of 4 lines, 2 lines as sampiran, and the next 2 lines as content by empowering sound elements to create aesthetics. (2) knowledge of the content and meaning of the parikan in kentrung art in the form of satirical value for those who are in love or romance, social, economic, cultural, or artistic issues; there is even mystical and religious value. (3) Knowledge related to the function of parikan includes: the function of a means of entertainment; a means of love for local culture; a means of caring for social, environmental, and safety functions.